Primary pulmonary lymphoma in children - Xiaohui Wu; Chunju Zhou; Ling Jin; Hui Liu; Jinrong Liu; Shunying Zhao (Orphanet Journal of Rare Diseases, 2019)
Abstract Background Primary pulmonary lymphoma (PPL) is a rare disease, especially in children. We analyse the clinical features of PPL in 4 children to strengthen a understanding of it. Results We reported a case series of 4 pediatric patients with PPLs including three diffuse large B-cell lymphomas and one natural killer-T cell lymphoma. All patients presented with unknown fever and cough as well as weight loss and fatigue. The white blood cell count was reduced in three patients and increased in the other one. The level of C-reactive protein was increased in all patients. The procalcitonin concentrations and bone marrow specimens were normal. Multiple or single pulmonary nodules with halo signs were found in all patients and air bronchograms found in 3 of them on chest computed tomography scan. Primary immunodeficiency was diagnosed in two patients who was performed genetic analysis. Conclusions When a patient presents with long-term fever, high C-reactive protein level, leukopenia/leukocytosis, and multiple or single pulmonary nodules with a “halo sign” and air bronchogram on computed tomography, a possibility of PPL should be considered. A co-existance of immunodeficiency needs to be further investigated in patients with PPL.